State Responsibility Towards The Rights of Customary Communities on Rempang Island from The Perspective of State Administrative Law (HTN) - Hutabarat, Chanrih; Abra, Emi Hajar; Hadiyanto, Alwan (Journal of Law, Politic and Humanities, 2025)
Rempang Island, as part of the administrative territory of Indonesia, is not exempt from constitutional dynamics. In the event of a case occurring on the island involving an abuse of authority, deviation from the principle of autonomy, or misalignment with constitutional implementation, constitutional law provides a framework to understand, analyze, and resolve such issues. This study aims to analyze whether the state has acted in accordance with the principles of good governance and constitutional justice in the case of Rempang Island, and to determine whether the state has involved indigenous communities in decision-making processes that directly affect their fate. The findings indicate that the development process of the Rempang Eco City project and the handling of the accompanying conflict have not fully complied with the principles of good governance and constitutional justice, particularly in relation to the rights of indigenous peoples, transparency, participation, and fairness. The conflict in Rempang Island stems from arbitrary government actions. The lack of transparency between the government and the community has led to misunderstandings between the two parties involved.